2013
DOI: 10.1186/1471-2253-13-45
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive aerosolized colistin for multi-drug resistant gram-negative pneumonia in the critically ill: a retrospective study

Abstract: BackgroundThe incidence of multi-drug resistant (MDR) gram-negative (GN) organisms including Pseudomonas and Acinetobacter spp has increased in the last decade, prompting re-evaluation of colistin for the management of these infections. Aerosolized colistin as an adjunct to intravenous therapy is a current option for the management of MDR-GN pneumonia, although data supporting this practice is limited. This study evaluates the efficacy of adjunctive aerosolized colistin in combination with intravenous colistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 22 publications
2
49
2
1
Order By: Relevance
“…Recently, Tumbarello et al also indicated that in 208 critically ill patients with HAP caused by MDR Gram negative organisms, aerosolized colistin as adjunct to intravenous form could significantly improve clinical cure rates and shorten the duration of mechanical ventilation, as compared with intravenous colistin monotherapy alone. 12 These studies were conflicting with earlier studies showing no significant differences with combination therapy; however they were criticized to have small number of patients leading to power limitations. 12,19,26 Efficacy of colistin can be enhanced with the use of another antibiotic, such as rifampicin or carbapenems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Tumbarello et al also indicated that in 208 critically ill patients with HAP caused by MDR Gram negative organisms, aerosolized colistin as adjunct to intravenous form could significantly improve clinical cure rates and shorten the duration of mechanical ventilation, as compared with intravenous colistin monotherapy alone. 12 These studies were conflicting with earlier studies showing no significant differences with combination therapy; however they were criticized to have small number of patients leading to power limitations. 12,19,26 Efficacy of colistin can be enhanced with the use of another antibiotic, such as rifampicin or carbapenems.…”
Section: Discussionmentioning
confidence: 99%
“…12 These studies were conflicting with earlier studies showing no significant differences with combination therapy; however they were criticized to have small number of patients leading to power limitations. 12,19,26 Efficacy of colistin can be enhanced with the use of another antibiotic, such as rifampicin or carbapenems. [27][28][29] Pintado et al reported that colistin use is effective in MDR Gram negative bacteraemia, with a response rate of 71.7%, when used in combination with aminoglycosides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…총 9개의 문헌 (randomized controlled trial 1개 27) , cohort 5개 [22][23][24][25][26] , case-control 3개 24,28,30) ) 중 8개 문헌에 대해서는 Newcastle-Ottawa Quality Assessment Scale을 1개의 문헌에 대해서는 Cochrane risk-of-bias tool을 사용하여 quality를 평 가하였고 그 결과는 Table 1에 제시하였다. 각 문헌의 quality assessment 결과 한 연구 참고문헌…”
Section: )unclassified